Leaf bacterial diversity mediates plant diversity and ecosystem function relationships - Laforest-Lapointe, Isabelle; Paquette, Alain; Messier, Christian; Kembel, Steven W. (Nature (London), 2017)
A tree biodiversity and ecosystem function experiment shows that leaf bacterial diversity is positively related to plant community productivity, and explains a portion of the variation in productivity that would otherwise be attributed to plant diversity and functional traits. Leaf bacteria promote plant production Biodiversity-ecosystem function studies have shown that plant species richness, functional diversity and functional identity are among the key factors driving terrestrial ecosystem productivity. Here, Isabelle Laforest-Lapointe and colleagues assess the contribution that leaf bacterial diversity makes to plant community production in a tree biodiversity-ecosystem function experiment carried out in Montreal, Canada. They find that leaf bacterial diversity is positively related to plant community productivity and explains a portion of the variation in productivity that would otherwise be attributed to plant diversity and functional traits. They conclude that biodiversity-ecosystem function relationships in plant communities could in part be driven by positive interactions that involve other trophic levels, including the plant microbiome. Research on biodiversity and ecosystem functioning has demonstrated links between plant diversity and ecosystem functions such as productivity 1 , 2 . At other trophic levels, the plant microbiome has been shown to influence host plant fitness and function 3 , 4 , and host-associated microbes have been proposed to influence ecosystem function through their role in defining the extended phenotype of host organisms 5 , 6 However, the importance of the plant microbiome for ecosystem function has not been quantified in the context of the known importance of plant diversity and traits. Here, using a tree biodiversity–ecosystem functioning experiment, we provide strong support for the hypothesis that leaf bacterial diversity is positively linked to ecosystem productivity, even after accounting for the role of plant diversity. Our results also show that host species identity, functional identity and functional diversity are the main determinants of leaf bacterial community structure and diversity. Our study provides evidence of a positive correlation between plant-associated microbial diversity and terrestrial ecosystem productivity, and a new mechanism by which models of biodiversity–ecosystem functioning relationships can be improved.